Targeted Delivery of Narrow-Spectrum Protein Antibiotics to the Lower Gastrointestinal Tract in a Murine Model of Escherichia coli Colonization - Carpena, Nuria; Richards, Kerry; Bello Gonzalez, Teresita D. J.; Bravo-Blas, Alberto; Housden, Nicholas G.; Gerasimidis, Konstantinos; Milling, Simon W. F.; Douce, Gillian; Malik, Danish J.; Walker, Daniel (Frontiers in Microbiology, 2021)
Bacteriocins are narrow-spectrum protein antibiotics that could potentially be used to engineer the human gut microbiota. However, technologies for targeted delivery of proteins to the lower gastrointestinal (GI) tract in preclinical animal models are currently lacking. In this work, we have developed methods for the microencapsulation of Escherichia coli targeting bacteriocins, colicin E9 and Ia, in a pH responsive formulation to allow their targeted delivery and controlled release in an in vivo murine model of E. coli colonization. Membrane emulsification was used to produce a water-in-oil emulsion with the water-soluble polymer subsequently cross-linked to produce hydrogel microcapsules. The microcapsule fabrication process allowed control of the size of the drug delivery system and a near 100% yield of the encapsulated therapeutic cargo. pH-triggered release of the encapsulated colicins was achieved using a widely available pH-responsive anionic copolymer in combination with alginate biopolymers. In vivo experiments using a murine E. coli intestinal colonization model demonstrated that oral delivery of the encapsulated colicins resulted in a significant decrease in intestinal colonization and reduction in E. coli shedding in the feces of the animals. Employing controlled release drug delivery systems such as that described here is essential to enable delivery of new protein therapeutics or other biological interventions for testing within small animal models of infection. Such approaches may have considerable value for the future development of strategies to engineer the human gut microbiota, which is central to health and disease.